New or rare Madagascar tiger beetles—26. A new species of the genus Pogonostoma Klug from northwestern Madagascar and a revised key to the Pogonostoma (P.) srnkai species-group (Coleoptera: Cicindelidae) - Moravec, Jiří; Wiesner, Jürgen; Jocque, Merlijn (Zootaxa, 2022)
A new species of the genus Pogonostoma Klug, 1835, P. (Pogonostoma) mahimborondrense Moravec & Wiesner sp. nov. is described as new to science from the Mahimborondro protected area in Northern Highlands, northwestern Madagascar. By its unique complex of diagnostic characters, the new species is incomparable to any other species within the genus. It is placed here into the Pogonostoma (P.) srnkai species-group (in the concept presented in the monograph of the genus by Moravec 2007). A revised key to species of the species-group is presented in order to supplement the key in the monograph. Habitus and diagnostic characters of the new species are illustrated in colour photographs. Maps and photos of the occurrence of the new species in Mahimborondro are also presented.